Jobs to Social Cohesion : Via Interests, Attitudes, and Identities - Kilroy, Austin (World Bank, Washington, DC, 2013)
The remit of this paper is to examine the link from jobs to social cohesion, focusing particularly on what kinds of jobs are most likely to improve social cohesion, and how policymakers can support those impacts. The paper suggests several qualitative mechanisms for a causal impact from particular aspects of jobs to social cohesion. In particular, jobs can help: (i) form diverse trust ties and friendships, (ii) diminish ignorance and prejudice towards other social groups, and (iii) create cross-cutting social identities based on occupation, firm or industry membership, which diminish the salience of other social cleavages. These mechanisms are subject to a number of scope conditions, as set out in the paper. Why are these insights relevant for public policy? First, because they show how crucial jobs can be to building social cohesion in a society. Second, because they point the way to some opportunities for public interventions to facilitate those links: particularly in terms of catalyzing interpersonal interactions through events like trade fairs and networking events, and in terms of encouraging social minorities to enter occupations and industries that have more frequent and intimate interpersonal interactions.